2020
DOI: 10.3390/cancers12082144
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Epidermal Growth Factor Receptor Sensitizes Glioblastoma Cells to Hypoxia-Induced Cell Death

Abstract: Background: The epidermal growth factor receptor (EGFR) signaling pathway is genetically activated in approximately 50% of glioblastomas (GBs). Its inhibition has been explored clinically but produced disappointing results, potentially due to metabolic effects that protect GB cells against nutrient deprivation and hypoxia. Here, we hypothesized that EGFR activation could disable metabolic adaptation and define a GB cell population sensitive to starvation. Methods: Using genetically engineered GB cells to model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It can be assumed that cancer cells cultured with the addition of epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), and nutritional supplements acquire certain properties, due to which the treatment with VV-GMCSF-Lact is more effective. Amplification of the epidermal growth factor receptor (EGFR) gene is known to be observed in more than 50% of glioblastoma cases [22]. The addition of EGF in the medium is able to stimulate the EGFR-dependent signaling pathways, such as phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that cancer cells cultured with the addition of epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), and nutritional supplements acquire certain properties, due to which the treatment with VV-GMCSF-Lact is more effective. Amplification of the epidermal growth factor receptor (EGFR) gene is known to be observed in more than 50% of glioblastoma cases [22]. The addition of EGF in the medium is able to stimulate the EGFR-dependent signaling pathways, such as phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, osimertinib inhibits the constitutive activity of EGFRvIII with high potency (< 100 nM) in a tyrosine kinase-dependent manner (31). In addition, it has been recently found that cells expressing mutant EGFRvIII are prone to starvation and hypoxia-induced cell death (32). This research supports the idea that using anti-VEGF agents that produce a low-oxygen environment could promote EGFRvIII-mutant hypoxiainduced cell death.…”
Section: Introductionmentioning
confidence: 59%
“…There is increasing experimental and clinical evidence that activation of EGFR and downstream signaling pathways render speci c subgroups of GBs vulnerable to hypoxia-inducing therapies. Hypoxia-induced cell death in GB models is preceded by ATP depletion, increase in glycolysis and higher levels of mitochondrial superoxides which have been associated with decreased metabolic ux and decreased NADPH/NADP + ratio (53). The di culty in effectively tackling tumor cells lies on the ample heterogeneity amongst various GB samples and models.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous report (47), mutant epidermal growth factor receptor variant III (EGFR vIII) mutation and EGFR overexpression glioma cells impaired physiological adaptation to starvation and rendered cells sensitive to hypoxia-induced cell death. Theoretically, the activation of EGFR enhances vulnerability to hypoxia-inducing therapies via a decrease in Nicotinamide adenine dinucleotide phosphate (NAPDH) levels.…”
Section: Mechanism Of Duration Of Bevacizumab Effectiveness In Light ...mentioning
confidence: 99%